Colivelin Rescues Ischemic Neuron and Axons Involving JAK/STAT3 Signaling Pathway. (15th September 2019) - Zhao, Hui; Feng, Yan; Wei, Changjuan; Li, Yan; Ma, Hongshan; Wang, Xuejiao; Cui, Zhigang; Jin, Wei-Na; Shi, Fu-Dong
Abstract: Colivelin is a neuroprotective humanin family peptide with potent long-term capacity against Aβ deposition, neuronal apoptosis, and synaptic plasticity deficits in neurodegenerative disease. We seek to investigate whether this effect of Colivelin also govern ischemic brain injury, and potential mechanism underlying the Colivelin-mediated action on ischemic neurons. We adopted 60 min induction of transient focal cerebral ischemia and reperfusion in mice. We found that relative to mice receiving vehicle, Colivelin administration decreased the neurological deficits and infarct lesion induced by brain ischemia. Colivelin inhibited axonal damage and neuronal death in brain tissue, which was associated with elevated anti-apoptotic gene expression in ischemic neurons as well as increased axonal growth up until two-weeks post-stroke. Moreover, Colivelin activated STAT3 signaling, which may partially contribute to its beneficial effect against neuronal death and axon growth. In conclusion, Colivelin induce anti-apoptotic genes up-regulation, and activate JAK/STAT3 signaling after ischemic stroke, which may contribute to its effects of rescuing ischemic neuronal death and axonal remodeling. This study may justify further works to examine Colivelin as a single or adjunct therapy in ischemic stroke. Highlights: Colivelin decreased neurological deficits and infarct lesion after brain ischemia. Colivelin inhibited axonal damage and neuronal death after ischemic stroke. Colivelin increased anti-apoptotic genes level via JAK/STAT3. Colivelin may serve as a single or adjunct therapy in ischemic stroke.